2015
DOI: 10.1590/1980-5497201500030009
|View full text |Cite
|
Sign up to set email alerts
|

Dental pain and associated factors in 2 to 4-year-old children in Goiânia

Abstract: ABSTRACT:Objective: To investigate the prevalence of dental pain and associated factors in 2-4-year-old children in Goiânia (GO). Methods: Cross-sectional study using home interviews with parents or guardians and anthropometric measures. The sample consisted of 385 children from 2 to 4 years old. The variables analyzed were: dental pain sometime in their lives, and demographic, socioeconomic and health-related factors (health condition, diet, nutritional status and behavior). Bivariate analysis and logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 15 publications
0
23
0
3
Order By: Relevance
“…Our study also revealed the association between overweight/obesity and the occurrence of dental pain, whereas overweight/obese children (aged 0 to 4.9 years old) had 1.12 the odds of experiencing dental pain as compared to their counterparts. A study by Lemes et al (2015) that was conducted on the 2 to the 4-year-old group of children revealed that one of the factors that were significantly related to the occurrence of dental pain was the consumption level of artificial powder juice containing sugar [57]. Even though the type of diet was not evaluated in the current study, yet, the result revealed by Lemes et al (2015) in their study might have provided us with the evidence of how this particular type of childhood diet might be one of the reasons that children who are overweight/obese have bigger odds on having dental pain symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also revealed the association between overweight/obesity and the occurrence of dental pain, whereas overweight/obese children (aged 0 to 4.9 years old) had 1.12 the odds of experiencing dental pain as compared to their counterparts. A study by Lemes et al (2015) that was conducted on the 2 to the 4-year-old group of children revealed that one of the factors that were significantly related to the occurrence of dental pain was the consumption level of artificial powder juice containing sugar [57]. Even though the type of diet was not evaluated in the current study, yet, the result revealed by Lemes et al (2015) in their study might have provided us with the evidence of how this particular type of childhood diet might be one of the reasons that children who are overweight/obese have bigger odds on having dental pain symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Lemes et al (2015) that was conducted on the 2 to the 4-year-old group of children revealed that one of the factors that were significantly related to the occurrence of dental pain was the consumption level of artificial powder juice containing sugar [57]. Even though the type of diet was not evaluated in the current study, yet, the result revealed by Lemes et al (2015) in their study might have provided us with the evidence of how this particular type of childhood diet might be one of the reasons that children who are overweight/obese have bigger odds on having dental pain symptoms. As previous studies have indicated how sugary beverages were significantly associated with overweight/obesity [58 -60] and the increased prevalence of dental caries [61 -63], which is the main cause of dental pain [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Toothache still causes negative impact on individuals' quality of life [20][21][22], therefore a greater orientation for pain relief and trauma care in PEDS is in fact expected [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies with young children evaluate toothache in terms of clinical aspects and/or socioeconomic issues addressed at the individual level (6)(7)(8)10). These individual clinical and socioeconomic factors have therefore already been well demonstrated in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Literature describes the prevalence of toothache in five-year-old children as being between 9.4% and 25.0% (1,(6)(7)(8)(9)(10). As cognitive ability is still developing in this age group, the evaluation of tooth pain is performed via the reports of parents (11).…”
Section: Introductionmentioning
confidence: 99%